Transposon Mutants of Bradyrhizobium japonicum Altered in Attachment to Host Roots - Vesper, Stephen J. (1987)
Transposon mutants of Bradyrhizobium japonicum 110 ARS were produced and screened for changes in attachment ability. Mutant CFK4 produced twice as many piliated cells, attached in 2.5-fold-higher numbers to soybean root segments, and colonized roots in about 2-fold-higher numbers than did the parental strain, 110 ARS. Mutants CFK35 and CFK38 were reduced in their attachment about 2-fold and 3.5-fold, respectively. This corresponded to reductions in piliated cells in their populations, reduced reaction with anti-pilus antiserum, and reduced hydrophobic attachment. Mutants CFK4 and CFK38 nodulated soybeans at about the same level as the parent strain, but CFK35 induced only pseudonodules. Two-dimensional gel analyses of the proteins from the mutants showed relatively few changes in proteins.